Pengaruh Corporate Governance, Dividend Policy, dan Karakteristik Perusahaan terhadap Nilai Perusahaan - Crysta, Michelle; Marlinah, Aan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine and obtain empirical evidence regarding the influence of institutional ownership, independent commissioners, dividend policy, debt policy, firm size, profitability, liquidity, and managerial ownership on firm value. In this study, firm value is measured using the Tobin's Q ratio. The research utilizes data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, with 45 companies selected as samples. A purposive sampling technique was employed to determine the sample, resulting in a total of 135 data points analyzed using multiple linear regression methods. The findings indicate that debt policy and profitability have a positive impact on firm value. Meanwhile, other independent variables, namely institutional ownership, independent commissioners, dividend policy, firm size, liquidity, and managerial ownership, were not found to significantly influence firm value. This study contributes particularly to companies by emphasizing the importance of debt composition and the ability to generate profits in attracting investors, as the results show that these two ratios significantly affect firm value.